LANGUAGE INTEGRATION AND SOCIAL ADAPTATION: PRACTICAL RESEARCH IN IMMIGRANT COMMUNITIES - Axatova Mohinisoxon Hasan qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the critical role of language integration in the social adaptation of immigrant communities. Language plays a pivotal role in facilitating communication, promoting cultural understanding, and fostering social cohesion among immigrants. By analyzing practical research, this paper highlights how language learning, maintenance of the native language, and bilingual practices contribute to social adaptation. Challenges such as linguistic discrimination, generational language shifts, and access to educational resources are discussed. Strategies for improving language integration and enhancing social participation are also proposed.